'Regent Suit' training improves recovery of motor and daily living activities in subjects with subacute stroke: a randomized controlled trial. (September 2013) - Monticone, Marco; Ambrosini, Emilia; Ferrante, Simona; Colombo, Roberto
Objective: To evaluate the efficacy of an elastic element-based suit, called 'Regent Suit', in improving the recovery of motor and daily living activities in patients experiencing a subacute stroke. Design: Randomized controlled trial. Setting: Neurorehabilitation unit. Subjects: Sixty patients with subacute stroke who were capable of walking without direct assistance were randomized to an experimental and control group. Interventions: The experimental group attended 20 sessions of neuromotor exercises (e.g. sit-to-stand, balance, gait training) wearing the 'Regent Suit'; the control group performed the same exercises without the 'Regent Suit'. Outcome measures: 6-minute walking test, Berg Balance Scale, the Functional Independence Measure, and the Barthel Index. The participants were evaluated before and after training, and after a further six months. Results: There were no significant between-group differences at baseline. A repeated measure linear mixed model revealed a significant effect of time ( p < 0.001), group ( p = 0.019), and time-by-group interaction ( p < 0.001) in the gait speed in favour of the experimental group. The Berg Balance Scale indicated a significant effect of time ( p < 0.001) and time-by-group interaction ( p < 0.001). The experimental group also showed greater improvement in Functional Independence Measure and Barthel Index. Discussion: The study findings showed that an intervention using the 'Regent Suit' is more effective than usual care in improving locomotion and daily living activities in patients with subacute stroke. Further studies might investigate the efficacy of this type of training in chronic stroke patients and the possibility of combining the suit with body weight-supported treadmill training.